2011
DOI: 10.5338/kjea.2011.30.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Characterization of Nano-emulsion Vitamin A, D and E (LaVita) in Rats

Abstract: BACKGROUND:Bioavailability enhancement by solubilization of lipophilic drugs in nano-emulsion has been reported and it may be useful in pharmaceutical and nutraceutical products. This study was performed to compare in vivo bioavailability of nano-emulsion formulation with that of the general product as control. METHODS AND RESULTS:The pharmacokinetics assessment of Vitamin A, D and E complex of nanoemulsion formulation (LaVita), in comparison to the general product, was performed in the male rat plasma by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In the present study, we show that consumption of VitD stably dispersed in a PPI nanoemulsion, created by sonication and pH shifting combined treatment as shown in our previous work [27] resulted Saponaria Molina, as surfactant and showed enhanced micellarization of VitD and absorption in rats [33]. Moreover, after single dose administration of nanoemulsified lipophilic vitamin mixture (i.e., vitamins A, D, E) to rats showed higher plasma area under the curve concentration for these vitamins compared to controls [34]. Though these studies inform on the bioavailability of vitamin D in nanoemulsions, it is important to consider its functionality and efficacy.…”
Section: Discussionsupporting
confidence: 68%
“…In the present study, we show that consumption of VitD stably dispersed in a PPI nanoemulsion, created by sonication and pH shifting combined treatment as shown in our previous work [27] resulted Saponaria Molina, as surfactant and showed enhanced micellarization of VitD and absorption in rats [33]. Moreover, after single dose administration of nanoemulsified lipophilic vitamin mixture (i.e., vitamins A, D, E) to rats showed higher plasma area under the curve concentration for these vitamins compared to controls [34]. Though these studies inform on the bioavailability of vitamin D in nanoemulsions, it is important to consider its functionality and efficacy.…”
Section: Discussionsupporting
confidence: 68%
“…In a recent study, Kadappan et al, (2018) created vitamin D-containing nanoemulsions using Q-NATURALE ® 200 V, an extract from Quillaia Saponaria Molina, as the surfactant and showed enhanced micellarization of VitD and absorption in rats [34]. Moreover, after single dose administration of nanoemulsified lipophilic vitamin mixture (i.e., vitamins A, D, E) to rats showed higher plasma area under the curve concentration for these vitamins compared to controls [35]. Though these studies inform on the bioavailability of vitamin D in nanoemulsions, it is important to consider its functionality and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Hatanaka et al [112] and Gong et al [114] carried out pharmacokinetic studies using in vivo analyses, and showed that nanoemulsified vitamin E was more bioavailable than its solid capsule forms, which again supports that nanoemulsion delivery systems are good canditates for enhancing bioavailability. Moreover, nanoemulsion delivery systems increased the antioxidant activities of natural vitamin E. The pharmacokinetic study after single dose administration to rat models showed that plasma concentration of the nanoemulsified lipophilic vitamin mixture (vitamins A, D, E) was higher when compared to the general products [113]. To summarize, nanoemulsions exhibit important role in enhancement of the bioavailability of lipophilic compounds with the advantages as below;…”
Section: Examples Of In Vivo Studiesmentioning
confidence: 97%
“…Hatanaka et al and Gong et al carried out pharmacokinetic studies using in vivo analyses, and showed that nanoemulsified vitamin E was more bioavailable than its solid capsule forms, which again supports that nanoemulsion delivery systems are good canditates for enhancing bioavailability. Moreover, nanoemulsion delivery systems increased the antioxidant activities of natural vitamin E. The pharmacokinetic study after single dose administration to rat models showed that plasma concentration of the nanoemulsified lipophilic vitamin mixture (vitamins A, D, E) was higher when compared to the general products . To summarize, nanoemulsions exhibit important role in enhancement of the bioavailability of lipophilic compounds with the advantages as below; The reduced size of nanoemulsion delivery systems promotes increased surface area and provides faster and extensive digestion. Enhanced solubilization rate of the bioactives into mixed micelles during the lipid digestion increases the bioaccessibility. Nanoemulsions facilitate the elimination of first‐pass metabolism and transfer of the chylomicron containing bioactive directly to lymphatic system. Designing nanoemulsion delivery systems with different surfactants/emulsifiers helps to enhance the intestinal permeation. Nanoemulsions may help to increase the residence time of the bioactive lipids within GIT by protecting them from the physicochemical changes and thus improve the absorption of these compounds by enterocyte cells. …”
Section: Bioavailability Of Lipophilic Vitamins Encapsulated In Nanoementioning
confidence: 99%
See 1 more Smart Citation